2016
DOI: 10.7196/samj.2016.v106i7.10549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 5 years of morbidity and mortality conferences in a metropolitan South African trauma service

Abstract: Background. Since 2008 the Pietermaritzburg Metropolitan Trauma Service (PMTS) has run a structured, self-reporting, metropolitan morbidity and mortality conference (MMC). In 2012 a hybrid electronic medical registry (HEMR) was introduced to capture routine data and to generate reports on morbidity and mortality. This paper reviews our experience in setting up a metropolitan MMC and compares the quality of the reported morbidity data from the pre-and post-HEMR era. Methods. We compared data from the MMC before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…The majority of the patients experiencing nursing-related morbidities were general surgery patients as these were the majority of the patients who were admitted to the service during the study period. The results showed that more males than females experienced nursing-related morbidities and this is in keeping with the results of a study by Kong and Clarke (2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The majority of the patients experiencing nursing-related morbidities were general surgery patients as these were the majority of the patients who were admitted to the service during the study period. The results showed that more males than females experienced nursing-related morbidities and this is in keeping with the results of a study by Kong and Clarke (2016).…”
Section: Discussionsupporting
confidence: 90%
“…The incident rate of 3.7% of nursing-related morbidity is consistent with the estimated rate of 2.5% to 18.4% found by Wilson et al (2012) in developing countries (including South Africa). Kong and Clarke (2016) reported an incident rate of 4.1% morbidities during a 5-year analysis of morbidity and mortality conferences in a South African trauma service. However, the incident rate of the current study is lower than the findings of 12.7% in the low- to middle-income countries revealed by Jha et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic database used to identify cases Auspitz et al, 19 Cromeens et al, 20 Gurien et al, 17 Hutter et al, 18 Kong and Clarke 34 Moderator selects cases Bhalla et al 32 Prospective proforma McVeigh et al 21 Attendance Improved faculty and resident attendance Teleconferencing Falcone and Watson, 38 Lewis et al 37 Morning meeting time Murayama et al 30 Dissemination Established systematic dissemination strategy Post-MMC newsletter Bhalla et al 32 PDCA cycle Vogel et al 40 Surgeon report cards Antonacci et al 41 MMC = morbidity and mortality conference; PDCA = plan-do-check-act; SBAR = situation, background, assessment, recommendation.…”
Section: Comprehensive Case Selectionmentioning
confidence: 99%
“…Regardless of the devastating complications associated with thoracic trauma, timely diagnosis and proper management can significantly reduce morbidity and mortality [9,10]. Accurate diagnosis of thoracic trauma depends on a high degree of suspicion and pattern recognition [11].…”
Section: Introductionmentioning
confidence: 99%